Benefits of spirituality and/or religiosity in patients with Chronic Kidney Disease: an integrative review - Ariane Moysés Bravin; Armando dos Santos Trettene; Luis Gustavo Modelli de Andrade; Regina Célia Popim (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: Identify and analyze existing evidence regarding the benefits of spirituality and / or religiosity in patients with Chronic Kidney Disease. Method: Integrative review carried out through consultation of databases: Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online, US National Library of Medicine and Scopus. The following descriptors were used: chronic kidney disease, spirituality and religion. Primary articles published by December 2017 were included. Results: Twenty-six articles were selected, from which four thematic categories emerged: benefits as a modality of coping, perception of quality of life, mental health and improvement of renal function after transplantation. Conclusion: Benefits included those related to situational coping modalities, such as the strengthening of hope, social support and coping with pain; those related to mental health, such as the lower risk of suicide and fewer depressive symptoms; improvement in the perception of quality of life and in renal function after transplantation.